Hydrodynamic Approach to Electronic Transport in Graphene: Energy Relaxation - Narozhny, B. N.; Gornyi, I. V. (Frontiers in Physics, 2021)
In nearly compensated graphene, disorder-assisted electron-phonon scattering or ``supercollisions'' are responsible for both quasiparticle recombination and energy relaxation. Within the hydrodynamic approach, these processes contribute weak decay terms to the continuity equations at local equilibrium, i.e., at the level of ``ideal'' hydrodynamics. Here we report the derivation of the decay term due to weak violation of energy conservation. Such terms have to be considered on equal footing with the well-known recombination terms due to nonconservation of the number of particles in each band. At high enough temperatures in the ``hydrodynamic regime'' supercollisions dominate both types of the decay terms (as compared to the leading-order electron-phonon interaction). We also discuss the contribution of supercollisions to the heat transfer equation (generalizing the continuity equation for the energy density in viscous hydrodynamics).